2013
DOI: 10.1155/2013/835426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Compliance with Institutional Preoperative Testing Guidelines for Minimal-Risk Patients Undergoing Elective Surgery

Abstract: Background. Few investigations preoperatively are important for low-risk patients. This study was designed to determine the level of compliance with preoperative investigation guidelines for ASA I patients undergoing elective surgery. Secondary objectives included the following: to identify common inappropriate investigations, to evaluate the impact of abnormal testing on patient management, to determine factors affecting noncompliant tests, and to estimate unnecessary expenditure. Methods. This retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Our findings are consistent with the conclusions of previous studies that report overuse of testing in the pre-operative setting, including studies of pre-operative cardiac stress test use among patients with Medicare, 2 medical consultations for cataract surgery, 3 and testing prior to hernia repair, 1 among other studies. 9,20 Though we found little evidence of guideline impact, it is noteworthy that rates of pre-operative testing have generally fallen over time. This likely reflects strong secular trends in testing, and may have been partially driven by temporal reductions in reimbursement.…”
Section: Discussionmentioning
confidence: 70%
“…Our findings are consistent with the conclusions of previous studies that report overuse of testing in the pre-operative setting, including studies of pre-operative cardiac stress test use among patients with Medicare, 2 medical consultations for cataract surgery, 3 and testing prior to hernia repair, 1 among other studies. 9,20 Though we found little evidence of guideline impact, it is noteworthy that rates of pre-operative testing have generally fallen over time. This likely reflects strong secular trends in testing, and may have been partially driven by temporal reductions in reimbursement.…”
Section: Discussionmentioning
confidence: 70%
“…Extension of TS expiration dates in outpatients who have not undergone transfusion significantly reduces the number of elective surgery patients going to the operating room without a valid TS. 23 Computerized decision support systems 24 and involvement of the anesthesiology team in presurgical planning 25 have also been shown to be beneficial in providing evidence-based presurgical testing. As well as studying services with high rates of inappropriate duplicate testing, it may also be beneficial to examine why some services have lower rates of inappropriate orders.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, they found that surgeons, more than anesthesiologists, order tests as a matter of routine resulting in a net increase in the cost per patient of 33.6% ( 27 ). Similarly, in a study of 1496 patients in Thailand, Siriussawakul et al found that only 12.1% of patients had preoperative workups that were in accordance with guidelines, with CMP/electrolytes being the most commonly ordered unnecessary test ( 26 ). In the UK, Phoenix et al estimated that inappropriate preoperative blood work resulted in an extrapolated cost of £11.2 million per year ( 28 ).…”
Section: Discussionmentioning
confidence: 99%